Integrating Peer Support into Mental Health Courses to Strengthen Student Self-Awareness: A Qualitative Case Study - Asriyanti Rosmalina (UIN Siber Syekh Nurjati Cirebon, 2026)
Mental health education for prospective counselors is still dominated by cognitive-oriented learning and has not optimally integrated reflective practices and structured peer support. This condition is important because self-awareness is a fundamental competency that must be possessed by prospective counselor students. Therefore, this study aims to explore how peer support can be integrated into the Mental Health course to strengthen the self-awareness of students of the Islamic Guidance and Counseling Study Program. This research uses a qualitative approach with an intrinsic case study design that is carried out in a class of Mental Health courses at UIN Siber Syekh Nurjati Cirebon. Data were collected through semi-structured interviews, focus group discussions, participatory observations, reflective journals, and document analysis, then analyzed using the Miles, Huberman, and Saldana interactive models. The results of the study show three patterns of peer support integration embedded in the curriculum, namely Experiential Learning Circle, Project-Based Digital Muhasabah, and Peer Counselor Mentoring. These various learning activities facilitate the development of student self-awareness through four interrelated phases, namely recognizing emotions, identifying cognitive patterns, building meanings based on Islamic values, and developing adaptive self-regulation strategies. The findings also show that peer support not only serves as a source of social support, but also as a reflective learning mechanism that encourages students' personal growth. This study concludes that the integration of peer support in mental health education is a meaningful pedagogical approach to strengthen students' self-awareness and offers a potential mental health learning model for Islamic religious universities.